Forearm Compartment Release with Incidental Soft Tissue Sarcoma - Chukwuemeka C. Ene, BS; Jason S. Salvato, BS; Matthew W. Parry, MD, MS; Alex Tang, MD; Michael S. Pheasant, MD; Aidan G. Papalia, DO, MBA; Jeffrey M. Gillette, DO (Journal of Hand Surgery Global Online)
Compartment syndrome is often trauma-related, but rare cases may arise from soft tissue sarcomas (STS) increasing pressure within muscle compartments. This case emphasizes the need to consider atypical causes of compartment syndrome in older adults. A 95-year-old woman with multiple health conditions presented with severe pain, swelling, and finger immobility following a minor twisting injury to her forearm. Examination findings suggested compartment syndrome, prompting an urgent fasciotomy to relieve pressure. Intraoperatively, a large mass was found within the volar compartment. Pathology identified it as a high-grade pleomorphic sarcoma. Given the patient’s age, health status, and comorbidities, observation was recommended instead of further surgery. This case highlights the importance of considering rare causes, like STS, in cases of compartment syndrome without clear trauma. Prompt surgical decompression provided pain relief, and the patient-centered, individualized approach to her follow-up reflects the balance needed between aggressive treatment and quality of life in elderly patients.